CAR-FINDING SYSTEM WITH COUCHDB-BASED SENSOR MANAGEMENT PLATFORM - Nocuń, Łukasz; Nieć, Michał; Pikuła, Paweł; Mamla, Aleksander; Turek, Wojciech (Computer Science, 2013)
Growing performance of low-cost mobile devices makes it possible to perform advancedprocessing on mobile sensors. This creates a need of building management system for groupsof sensors actively analyzing signals from hardware devices. In this paper an architectureof a CouchDB-Based Sensor Management Platform is presented and its application for theproblem of ﬁnding stolen cars is shown. Detailed performance tests of the platform and itsapplication are provided.